(untitled) (Journal of International Studies, 2019)
Democratic Peace Theory has been one of the most hotly debated topics ever since the 1980s. From Kant to the present day, the meaning of Democratic Peace Theory has changed, while the theory nowadays claims in principle that democratic states wage war against each other less often owing to their institutions’ and citizens’ abilities to urge their governments to establish a peaceful foreign policy. At this point, the critical theory offers an alternative explanation for the behaviors of democratic countries. This study was designed as a theoretical discussion utilising the analysis of primary and secondary sources in the field, both in printed and electronic materials. Employing the viewpoint of the critical theory, this paper argues that Democratic Peace is the disguise of hegemonic relations and the product of the historical block. This study revealed that democracies are not pacifist actors in the international realm. As articulated by the critical approach, the study also puts forth that the concept of Democratic eace facilitates the expansionist ambitions of hegemonic powers in the international system by utilizing various humanitarian interventions and serves as a means to maintain imperialist peace. Empirical evidence from the military intervention in Libya further reinforces this argument. Thus, this study asserts the idea to be cautious against the propositions of the Democratic Peace Theory because any activities done in the name of spreading democracy may involve a hidden agenda and disrupt the internal stability of non-democratic countries.